Insulin-Like Growth Factor (IGF) Pathway Targeting in Cancer: Role of the IGF Axis and Opportunities for Future Combination Studies - Simpson, Aaron; Petnga, Wilfride; Macaulay, Valentine M.; Weyer-Czernilofsky, Ulrike; Bogenrieder, Thomas (Targeted oncology, 2017)
Despite a strong preclinical rationale for targeting the insulin-like growth factor (IGF) axis in cancer, clinical studies of IGF-1 receptor (IGF-1R)-targeted monotherapies have been largely disappointing, and any potential success has been limited by the lack of validated predictive biomarkers for patient enrichment. A large body of preclinical evidence suggests that the key role of the IGF axis in cancer is in driving treatment resistance, via general proliferative/survival mechanisms, interactions with other mitogenic signaling networks, and class-specific mechanisms such as DNA damage repair. Consequently, combining IGF-targeted agents with standard cytotoxic agents, other targeted agents, endocrine therapies, or immunotherapies represents an attractive therapeutic approach. Anti-IGF-1R monoclonal antibodies (mAbs) do not inhibit IGF ligand 2 (IGF-2) activation of the insulin receptor isoform-A (INSR-A), which may limit their anti-proliferative activity. In addition, due to their lack of specificity, IGF-1R tyrosine kinase inhibitors are associated with hyperglycemia as a result of interference with signaling through the classical metabolic INSR-B isoform; this may preclude their use at clinically effective doses. Conversely, IGF-1/IGF-2 ligand-neutralizing mAbs inhibit proliferative/anti-apoptotic signaling via IGF-1R and INSR-A, without compromising the metabolic function of INSR-B. Therefore, combination regimens that include these agents may be more efficacious and tolerable versus IGF-1R-targeted combinations. Herein, we review the preclinical and clinical experience with IGF-targeted therapies to-date, and discuss the rationale for future combination approaches as a means to overcome treatment resistance.